ChemInform Abstract: CuCrO2 Delafossite: A Stable Copper Catalyst for Chlorine Production. Issue 52 (24th December 2013) - Amrute, Amol P.; Larrazabal, Gaston O.; Mondelli, Cecilia; Perez‐Ramirez, Javier
Abstract Single‐phase cuprous delafossites CuMO2 (M: Cr, Al, Ga, Fe, Mn) are synthesized by solid state reaction of equimolar mixtures of Cu2O and M2O3 (1273—1423 K, 30 h).